Foundation Expression Blend 4 with Silverlight - Gaudioso, Victor; Brown, Tracy; Renow-Clarke, Ben.; Collins, Corbin; Andres, Clay.; Anglin, Steve; Beckner, Mark.; Buckingham, Ewan.; Cornell, Gary.; Gennick, Jonathan; Hassell, Jonathan; Lowman, Michelle; et al. (Berkeley, CA : Apress, 2010)
Foundation Expression Blend 4 with Silverlight takes you through your first steps in creating rich Internet applications (RIAs) using the latest release of Microsoft$1 (Bs technology. You$1 (Bll explore features such as custom user controls that you can reuse throughout your projects and the media element that allows you to easily add sound and video to your applications. Silverlight 4 enables you to rapidly develop compelling, cross-platform RIAs using the extensive .NET 4 libraries, the powerful, design friendly Blend 4 integrated development environment (IDE), and an enhanced workflow that allows designers and developers to work on the same set of files at the same time. At the end, you$1 (Bll put everything you have learned together to create a sample Silverlight 4 website. Whether you$1 (Bre an experienced .NET or web developer, or you$1 (Bre just starting out, this book will provide you with all you need to create RIAs with Expression Blend 4. Develop stunning RIAs in a short time using Blend 4 and Silverlight 4. Learn basic object-oriented programming principles. Get familiar with the Blend 4 development environment.s
Setting Up the Silverlight Development Environment -- The Blend Integrated Development Environment -- C#, XAML, and Object-Oriented Programming -- Layout Controls: Including the New Silverlight 4 Controls: Viewbox, RichTextBox, FlowDirection Property, and Improved Data Binding -- Timed Storyboards: Creating a Newton Cradle Application -- Using VSM and Blend 4$1 (Bs State Panel to Create a Silverlight Media Player -- Behaviors in Silverlight -- The Silverlight MediaElement: Create a Video Player with a Custom UserControl, XML De-serialization, and Behaviors -- Events and EventHandlers -- Classes and Interfaces -- Styles, Control Templates, and Custom UserControls -- Writing a Custom Content Panel -- Writing ailverlight 4 Out-Of-Browser Application with Elevated Trust and the New Silverlight 4 COM API -- Creating a Photobooth Application with the Silverlight 4 Webcam API -- MVVM: Model-View-ViewModel -- SketchFlow Prototyping -- New Features of Silverlight 4.s
Keywords: Computer science; Computer Science; Computer Science, general